2008
DOI: 10.1634/stemcells.2007-0389
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-511 but Not -332, -111, or -411 Enables Mouse Embryonic Stem Cell Self-Renewal In Vitro

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 37 publications
6
112
0
Order By: Relevance
“…Basement membranes have been found to affect stem cell as well as tissue behavior and may play useful roles in driving stem cells down differentiation pathways and in the maintenance of biological activity and stability of engineered tissues. It has recently been discovered, for example, that recombinant laminin-511 is an outstanding substrate to maintain mouse and human stem cells in a pluripotent state, whereas the laminin in a more complex environment has been reported to drive pancreatic differentiation (Domogatskaya et al 2008;Higuchi et al 2010;Rodin et al 2010). Basement membrane components are also being used to modify the surface properties of biomimetic materials for use in tissue engineering, e.g., nerve conduits (reviewed in von der Mark et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Basement membranes have been found to affect stem cell as well as tissue behavior and may play useful roles in driving stem cells down differentiation pathways and in the maintenance of biological activity and stability of engineered tissues. It has recently been discovered, for example, that recombinant laminin-511 is an outstanding substrate to maintain mouse and human stem cells in a pluripotent state, whereas the laminin in a more complex environment has been reported to drive pancreatic differentiation (Domogatskaya et al 2008;Higuchi et al 2010;Rodin et al 2010). Basement membrane components are also being used to modify the surface properties of biomimetic materials for use in tissue engineering, e.g., nerve conduits (reviewed in von der Mark et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This method can facilitate the development of cells lines for human cell therapy purposes. We have previously shown that human recombinant LN-511, which is expressed in the blastocyst inner cell mass, alone can support monolayer cultures and self-renewal of both mouse ES 7 and human pluripotent ES and iPS cells 4 . The present results show that LN-521 provides a more robust substratum for renewal of hES cells and additionally in combination with E-cadherin permits their efficient clonal expansion not enabled by LN-511.…”
Section: Discussionmentioning
confidence: 99%
“…The assay was performed as described previously 7 . Briefly, 96-well plates were coated by extracellular matrix proteins as described above and blocked by O3 medium containing bovine serum albumin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in particular the case of Foxd-3 which has been found to be required for the maintenance of pluripotent cells in the mouse embryo 236 as well as of laminin 10/11 (also known as laminin 511) which has been found to promote mouse embryonic stem cell renewal. 237 Indeed, the laminin α5 chain has been previously identified in a screen for genes upregulated in response to chick truncal NC induction. 35 Interestingly, laminin a5 null mice display anomalies suggestive of a role in the maintenance of NC cells into a progenitor state.…”
Section: Lineage Decisions and Emtmentioning
confidence: 99%